Mechano-electrochemical interaction for pipeline corrosion: A review - Wang, Yicheng; Xu, Luyao; Sun, Jialin; Cheng, Y. Frank (Journal of Pipeline Science and Engineering, 2021)
•Define the thermodynamics and kinetics of mechano-electrochemical interaction for pipeline corrosion.•Quantitatively determine the effects of elastic and plastic deformations on pipeline corrosion.•Develop a mechano-electrochemical interaction based multiple physics field coupling model for pipeline corrosion prediction.•Review the state-of-the-arts of pipeline corrosion under stressing conditions.•Identify further research topics in mechano-electrochemical interaction during corrosion. Engineering structures such as pipelines usually operate under stressing conditions. When corrosion occurs on the structures in service environments, the stress and corrosion reactions synergistically result in a so-called mechano-electrochemical (M-E) interaction, adversely affecting the structural integrity. This work reviewed the fundamentals of the M-E interaction for pipeline corrosion, where both corrosion thermodynamics and kinetics were derived by incorporating the effect of stress and strain applied on the pipelines. Under an elastic deformation, the M-E interaction for pipeline corrosion is usually negligible, while a dynamic elastic stress can degrade the integrity of corrosion scale on the steel and slightly accelerates the steel corrosion. However, plastic deformation results in an appreciable M-E interaction, remarkably changing both corrosion potential and corrosion rate of pipeline steels. Based on the M-E interaction theory, a multi-physics field coupling model with finite element analysis was developed to assess corrosion defects on pipelines for failure prediction. Perspectives of the M-E interaction in pipeline corrosion research and preventive management were analyzed.